Editorial - Quayum, Mohammad Abdul (International Islamic University Malaysia, 2012)
This is the tenth issue and the second thematic issue of Asiatic. After publishing a special issue on Southeast Asian literature in December 2011, we thought we should devote our next issue to South Asian literature. Accordingly, I invited Professor Fakrul Alam to help me in the process. It was not difficult to ascertain Professor Alam as the potential guest editor for the issue as he has several well-known publications in the field. Since his book on Bharati Mukherjee in Twayne’s Contemporary United States Authors Series in 1996, Professor Alam has also compiled and edited the volume South Asian Writers in English, in the Thomson-Gale “Dictionary of Literary Biography” series (2006), and more recently a volume on Rabindranath Tagore, The Essential Tagore, published concurrently by the Harvard University Press and Visva-Bharati University in 2011...